2015
DOI: 10.1007/s00253-015-7241-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of aquifer thermal energy storage and enhanced bioremediation: resilience of reductive dechlorination to redox changes

Abstract: To meet the demand for sustainable energy, aquifer thermal energy storage (ATES) is widely used in the subsurface in urban areas. However, contamination of groundwater, especially with chlorinated volatile organic compounds (CVOCs), is often being encountered. This is commonly seen as an impediment to ATES implementation, although more recently, combining ATES and enhanced bioremediation of CVOCs has been proposed. Issues to be addressed are the high water flow velocities and potential periodic redox fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 96 publications
(112 reference statements)
1
12
0
Order By: Relevance
“…Finally, a combination of ATES and remediation is considered a promising new concept to achieve both energy savings and improvement of the groundwater quality [73]: however, the presence of soil and/or groundwater contaminants in many urban environments may limit applicability of ATES and hampers redevelopment of these sites.…”
Section: Cold Water Sources: Flowrate and Temperature Limitationsmentioning
confidence: 99%
“…Finally, a combination of ATES and remediation is considered a promising new concept to achieve both energy savings and improvement of the groundwater quality [73]: however, the presence of soil and/or groundwater contaminants in many urban environments may limit applicability of ATES and hampers redevelopment of these sites.…”
Section: Cold Water Sources: Flowrate and Temperature Limitationsmentioning
confidence: 99%
“…Among the various combination concepts, in-situ treatment of the contaminated subsurface by thermally enhanced bioremediation has received the most attention. Several studies using experimental (Ni et al, 2015a;Ni et al, 2015b), field (Pellegrini et al, 2019) and modeling (Moradi et al, 2018;Roohidehkordi and Krol, 2021) approaches have demonstrated a good potential of combining UTES and biodegradation. Nevertheless, another potential remediation strategy, which is the enhanced volatilization of contaminants from groundwater and subsequent release to the atmosphere, has received relatively little attention in combination with UTES.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have also been performed, including field monitoring, numerical modeling, management and operating strategy, ,, and policy, , to analyze the efficiency of ATES and seek possible improvements and optimizations. Recently, the combination of ATES and in situ bioremediation (ATES–ISB) has gained attention due to its potential for simultaneously dealing with energy and environmental problems. ,,, The ATES–ISB system is being investigated for the sustainable redevelopment of urban brownfields with energy demand and encountering groundwater contaminated by chlorinated volatile organic compounds (CVOCs). Previous laboratory studies have revealed that complete CVOC biodegradation not only proceeds under the high flow condition of ATES but also shows a 13-fold improvement with simulated ATES functioning .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of ATES and in situ bioremediation (ATES–ISB) has gained attention due to its potential for simultaneously dealing with energy and environmental problems. ,,, The ATES–ISB system is being investigated for the sustainable redevelopment of urban brownfields with energy demand and encountering groundwater contaminated by chlorinated volatile organic compounds (CVOCs). Previous laboratory studies have revealed that complete CVOC biodegradation not only proceeds under the high flow condition of ATES but also shows a 13-fold improvement with simulated ATES functioning . In addition, Ding et al considered ATES as a new source for thermally enhanced bioremediation, while two ongoing pilots also demonstrated a successful application of the ATES–ISB system under field conditions. ,, Although these findings put forward that ATES–ISB can serve as a new and sustainable approach for urban brownfield redevelopment, to what extent such a combined system is more sustainable than the conventional techniques or whether it is truly more environmentally friendly requires investigation.…”
Section: Introductionmentioning
confidence: 99%